Analysis of the Disharmony of Regulations between the Obligation of Confidentiality of Notary Protocols and the Fulfillment of the Rights of Personal Data Subjects from the Perspective of the Notary Law and the Personal Data Protection Law - Aria Roby Putra; Rika Kurniaty; Letizia Dessy Andreassari (JURNAL AKTA, 2026)
The development of personal data protection regulations in Indonesia through Law Number 27 of 2022 concerning Personal Data Protection has legal consequences for various sectors that process personal data, including notarial practices. Notaries, as public officials authorized to make authentic deeds, have a legal obligation to maintain the confidentiality of notarial protocols as regulated in Article 16 paragraph (1) letters b and f of Law Number 2 of 2014 concerning the Position of Notary. On the other hand, Article 8 of the personal data protection law provides a number of rights to data subjects, such as the right to terminate processing, delete, and/or destroy personal data. The meeting between these two legal regulations has the potential to cause disharmony of norms, especially when the fulfillment of the rights of personal data subjects conflicts with the notary's obligation to maintain the confidentiality of notarial documents that are part of the notarial protocol. This study aims to analyze the legal implications of this disharmony of regulations and formulate a construction of harmonization of norms between the obligation to confidentiality of notarial protocols and the fulfillment of the rights of personal data subjects from a positive legal perspective in Indonesia. The research method used is normative legal research with a statutory and conceptual approach. The results of the study indicate that the disharmony between the two regulations creates potential conflicts of obligations for notaries in practice, particularly regarding granting access to or deleting personal data contained in authentic deeds. Harmonization of norms can be achieved through a systematic interpretation of both laws, the application of the principle of proportionality in limiting data subjects' rights, and strengthening standards for personal data management in notarial practice. This approach allows for a balance between protecting individual privacy rights and the legal certainty inherent in notarial documents as authentic evidence.